Situational Strategic Planning in the teaching-learning of the medical professionals during Emergency Remote Learning: experience report (Research, Society and Development, 2023)
Acute Chagas Disease presents an alarming epidemiological situation in the Northern Region of Brazil. This is mainly due to the perennial neglect of prevention and prophylaxis by social agents responsible for public health. The curricular content of the medical school of the Federal University of Pará contemplates, in the Longitudinal Axis of Comprehensive Health Care of the Individual, Family and Community, the teaching of Strategic Situational Planning in the exercise of programming actions to promote health and prevent diseases and illnesses. This experience report aimed, in a moment of Emergency Remote Teaching, to identify the importance of teaching-learning this type of strategy for medical students. During the experience in applying the simplification of the planning method proposed by Artmann (2000), there was a great adherence from the students, and it brought them closer to the formatting of an Intervention Project where the operations and actions were based on the goals of positive changes in the indicators that stated the problem, besides the protagonism in the literature review for knowledge of Acute Chagas Disease and its epidemiological surveillance. The elaboration of the program also provided the reflection on humanized care, which encouraged the students to exercise proactivity and solidarity to circumvent local problems that can hinder the work focused on the welfare of a community.